MANAGEMENT OF TEMPORO MANDIBULAR DISORDER (TMD) IN PATIENT WITH LOW VERTICAL DIMENSION AND DEEP ANTERIOR BITE - Henni Koesmaningati; Laura Susanti Himawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The cases of TMD are complex and multifactorial, therefore the management should be done by several disciplines. In this report, a 27-year-old man came to the teaching hospital of the University of Indonesia Faculty of Dentistry's Prosthodontic Department complaining about clicking sound and pain around his right joint. He received orthodontic treatment 9 years ago with removable appliance at a private practice and had 4 premolar extractions. The patient's face looked asymmetric, with a low vertical dimension, a Class II occlusion, and an anterior deep bite. Besides that, he clenched his teeth during emotional stress. Lateral transcranial photo showed that the position of the left condyle was relatively normal or slightly anterior, and the right condyle was in the superoposterior position in the fossa with an abnormal shape. To solve this problem, the patient was referred to the Orthodontic Department to get a correct vertical dimension and normal anterior overbite. After 6 years, the patient was again referred to the Prosthodontic Department, but the result was not successful. In order to get the right vertical dimension, an occlusal splint was fabricated to achieve a comfort jaw relation. In this position, the overbite was 2 mm, but the space between the upper and lower posterior teeth was 5 mm. In this situation, full veneer crowns were not impossible to fabricate. Finally, to maintain this comfort position, the patient was suggested to wear the occlusal splint and come regularly for control every 6 months.